Pelatihan Karya Tulis Ilmiah Bagi Mahasiswa - Deddy Yusuf Yudhyarta; Erma Susanti; M. Ilyas (STAI Auliaurrasyidin Tembilahan, 2021)
The purpose of this training was the preparation of scientific writing and assistance in the practice of writing a research paper. The output will be in the form of a proposal and a draft report. This training activity was carried out for a month, In the first session, trainees were given different materials and assignments for writing scientific papers. In the second stage, participants were required to write scientific papers using mentoring, participatory, and guided methods. In the third stage, participants collected their assignments followed by discussions involving all personnel and training participants. This community service was carried out for sixth-semester students who were also studying their research papers at STAI Auliaurrasyidin Tembilahan.